Sustainability : A Biological Perspective / [electronic resource] - Morse, Stephen (Cambridge : Cambridge University Press, 2010)
Encouraging students to engage in the challenges and complexity of sustainability, this text considers not only the theories underlying sustainability, but more importantly how theories are translated into practice and the difficulties of achieving this in the world in which we live. This pragmatic focus gives students a greater understanding of the practice of sustainability and highlights the challenges involved. Models and theories are illustrated throughout with real world examples to help students move away from the abstract and connect with genuine issues. The text begins by focusing on sustainable production and consumption and how they are related. The role of tools such as modelling and sustainability indicators are explored, and extended into the fields of stakeholder participation, livelihoods and evidence-based policy. The final chapter explores the interconnections between apparently disparate subjects and the importance of taking an interdisciplinary perspective.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Sustainability; Sustainable development